Integrated optimization of pretreatment conditions for bioethanol production from steam treated triticale straw - Agudelo Aguirre, Roberto Arturo (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.